Menelisik Tafsir Al-Jâmi’ Li Ahkâm Al-Qurân Karya Al-Qurthubi: Sumber, Corak dan Manhaj - Abdul Rohman; Ahmad Jalaluddin Rumi Durachman; Eni Zulaiha (Jurnal Kawakib, 2022)
This article discusses the special way (manhaj) from the book of interpretation of al-Jâmi' li ahkâm al-Qurân by Al-Qurtubi. The purpose of this paper is to find out what sources are used as references by al-Qurtubi, how the style of his interpretation is and how the special way (manhaj khâsh) adopted by Al-Qurtubi in implementing his interpretation. The writing of this research will be based on literature review or library research, using qualitative methods. The main source (primary) that is used as reference material is the book of interpretation of al-Jâmi' li ahkâm al-Qurân by Imam Al-Qurtubi, while the additional (secondary) source is derived from the books of interpretation of the Qur'ran and other relevant books with the topic of discussion. This research is exploratory research. The results obtained are that the sources of al-Qurtubi's interpretation are the Qu'ran, the sunnah of the Prophet, the opinions of Sahabah and the opinions of tabi'in, the history of asbâb an-nuzûl, Arabic poems, qiraat, opinions of madzhab scholars, books of interpretation of previous scholars. , such as the works of Az-Zujaj, ma'ânî al-qurân; Abu Ubaidah, majâz al-qurân; Al-Harasi, ahkâm al-qurân; and others. In addition, Al-Qurtubi also quotes from the books of hadith, such as the nine books (kutub at-tisáh); Sunan books, Musnads, and also the Maghazi books. The style of interpretation is fiqhi interpretation and there are ten khâsh manhajs taken by Al-Qurtubi in his commentary book.